Analytical approximate solution of Carleman's equation by using Maclaurin series - Yaghobifar, Mohammad; Nik Long, Nik Mohd Asri (Hikari, 2010)
In this paper we introduce a expansion method for solution of carleman's equation, in this method we expand the known function as a Maclaurin series and convert the solution into linear combination of some elements. We proved this linear combination is uniformly convergence to the analytic solution. If the known function be a polynomial then we have exact solution.